2015
DOI: 10.4103/1658-354x.152838
|View full text |Cite
|
Sign up to set email alerts
|

Role of regional anesthesia for placement of peritoneal dialysis catheter under ultrasound guidance: Our experience with 52 end-stage renal disease patients

Abstract: Aim:The number of patients with end-stage renal disease (ESRD) has shown a consistent rise in India in recent years. Continuous ambulatory peritoneal dialysis (CAPD) remains one of the safe and effective forms of treatment. In this study, we have tried to assess the effectiveness of field block technique for analgesia during catheter placement surgery until 24 h postoperatively, also, if it can obviate the need for general anesthesia in these high-risk patients.Materials and Methods:We studied 52 ESRD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…The dosage of ropivacaine used in our study was similar or even lower when compared with that mentioned in the previous studies [20,21,23,24]. The blood level and safety range data of local anesthetic in TAP blocking is still lacking in ESRD patients, which demands to be explored in future studies.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…The dosage of ropivacaine used in our study was similar or even lower when compared with that mentioned in the previous studies [20,21,23,24]. The blood level and safety range data of local anesthetic in TAP blocking is still lacking in ESRD patients, which demands to be explored in future studies.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies also showed remarkable analgesic effect of TAP block till 24 h after PDC implantation [20,21,23]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the once hypothetical idea of peritoneal opening under local anesthetic infiltration became routine in many operating rooms around the world, saving a multi-morbid ESRD patient from the many risks of intubation [12]. This method is usually done through an ultrasound-guided Transversus abdominis plane (TAP) block, a method which has been thoroughly described and studied, and while feasible holds a high risk of conversion to general anesthesia (GA) [13][14][15][16][17]. Another approach also describes the laparoscopic insertion of the Tenckhoff catheter employing nitrous oxide to create a pneumoperitoneum under local anesthetic infiltration [18].…”
Section: Introductionmentioning
confidence: 99%